Arcangeli's type discrepancy principles for a class of regularization methods using a modified projection scheme - M. T. Nair; M. P. Rajan (Abstract and Applied Analysis)
Solodkĭ (1998) applied the modified projection scheme of Pereverzev (1995) for obtaining error estimates for a class of regularization methods for solving ill-posed operator equations. But, no a posteriori procedure for choosing the regularization parameter is discussed. In this paper, we consider Arcangeli's type discrepancy principles for such a general class of regularization methods with modified projection scheme.